Commercial airplane design principles - Sforza, P. M. (Butterworth-Heinemann, 2014)
Commercial Airplane Design Principles is a succinct, focused text covering all the information required at the preliminary stage of aircraft design: initial sizing and weight estimation, fuselage design, engine selection, aerodynamic analysis, stability and control, drag estimation, performance analysis, and economic analysis. The text places emphasis on making informed choices from an array of competing options, and developing the confidence to do so. Shows the use of standard, empirical, and classical methods in support of the design process Explains the preparation of a professional quality design report Provides a sample outline of a design report Can be used in conjunction with Sforza, Commercial Aircraft Design Principles to form a complete course in Aircraft/Spacecraft Design.